PREDICTIVE ABILITY OF INTERIM ANNOUNCEMENTS BY USING MEAN DEVIATION TESTING - Rexon Nainggolan (Jurakunman (Jurnal Akuntansi dan Manajemen), 2018)
The study examines the predictive ability of interim announcement on projecting year-end financial statements. The investigation tests the accuracy of projected income statements by using proportional method of Q1, Q2, and Q3 interim announcements against actual year-end.The study investigates 280 announcements from 70 of 415 firms listed in Indonesia Stock Exchange. The indicators being measured are the income statements components which include revenue, expense, other income/loss, net income, and earning per share (EPS) of the interim announcements. The study uses mean deviation as tools on measurements.The finding indicates that income statements reported in the interim announcements, if projected proporsionally, deviate signifantly against the actual year-end (Q4), in most type of industries, which reflected by the significant mean deviation. The conclusion is consistent in all main components of income statements tested, including sales, expenses, other income/loss, net income, and earning per share (EPS). However, the study indicates that eventhough the deviation is still signicant, it is reduced in Q2 and Q3 as the periods are longer.Keywords: interim announcement, mean deviation, Indonesian Stock Exchange